Impact of graded dietary fumonisin contamination levels on the growth performance and selected health indices of turbot (Psetta maxima). Issue 1 (2nd January 2022) - Gonçalves, Rui A.; Dias, Jorge; Serradeiro, Renata; Schatzmayr, Dian
ABSTRACT: A common problem that arises from the use of plant ingredients is the presence of mycotoxins. The plant meals with more potential to be used in turbot diets have a natural tendency to be contaminated by fumonisins (FUM). Psetta maxima fed: FUM 1.0, FUM 2.0 and FUM 5.0 mg kg −1 diets showed a significantly lower final mean body weight, specific growth rate and protein efficiency ratio, and a concomitantly higher feed conversion ratio, than those fed the Control or FUM 0.5 diet. At dietary concentrations of 1 to 5 mg kg −1, FUMs caused a reduction of the brush border villi length in the distal intestine and a reduction of hepatic lipid inclusion. In conclusion, dietary FUM contamination over the course of 63 days, lead to significant damaging effects on the overall growth performance, nutrient retention, organ morphology and immune status of turbot.